Extractive Spectrophotometric Determination of Micro Amounts of Nickel(II) Using Benzildithiosemicarbazone - Krishna Reddy, B.; Varada Reddy, A. (Asian Journal of Chemistry, 2010)
Nickel(Il) reacts with benzilditbiosemicarbazone in aqueous dimethyl formamide solution in ammonium chloride ammonium hydroxide buffer of pH 9.0 giving yellowish orange precipitate. The 1 : 1 complex in chloroform has a maximum absorption at 410 nm and is stable for 48 h. Beer's law is obeyed in the range 0.1-1.6 μg/ml of nickel(II). The effect of various foreign ions is also studied. The method is applied for the estimation ot micro amounts of nickel(lI) in nichrome wire and steel samples and the results are compared with atomic absorption spectrophotometric method.